Comparison of Three Different Aqueous Microenvironments for Enhancing Oral Bioavailability of Sildenafil: Solid Self-Nanoemulsifying Drug Delivery System, Amorphous Microspheres and Crystalline Microspheres - Kim JS (Dove Medical Press, 2021)
Jung Suk Kim,1,* Fakhar ud Din,2,* Sang Min Lee,1,* Dong Shik Kim,1 Mi Ran Woo,1 Seunghyun Cheon,1 Sang Hun Ji,1 Jong Oh Kim,3 Yu Seok Youn,4 Kyung Taek Oh,5 Soo-Jeong Lim,6 Sung Giu Jin,7 Han-Gon Choi1 1College of Pharmacy, Hanyang University, Ansan, South Korea; 2Department of Pharmacy, Quaid-I-Azam University, Islamabad, Pakistan; 3College of Pharmacy, Yeungnam University, Gyongsan, South Korea; 4School of Pharmacy, Sungkyunkwan University, Suwon, South Korea; 5College of Pharmacy, Chung-Ang University, Seoul, South Korea; 6Department of Bioscience and biotechnology, Sejong University, Seoul, South Korea; 7Department of Pharmaceutical Engineering, Dankook University, Cheonan, South Korea*These authors contributed equally to this workCorrespondence: Sung Giu Jin; Han-Gon Choi Tel +82 41-550-3558; +82 31-400-5802Fax +82 41-559-7945; +82 31-400-5958Email sklover777@dankook.ac.kr; hangon@hanyang.ac.krBackground: The purpose of this study was to screen various drug delivery systems for improving the aqueous solubility and oral bioavailability of sildenafil. Three representative techniques, solid self-nanoemulsifying drug delivery systems (SNEDDS), amorphous microspheres and crystalline microspheres, were compared.Methods: Both microspheres systems contained sildenafil:Labrasol:PVP at a weight ratio of 1:1:6. The amorphous microspheres were manufactured using ethanol, while crystalline microspheres were generated using distilled water. Liquid SNEDDS was composed of sildenafil:Labrasol:Transcutol HP:Captex 300 in the ratio of 1:70:15:15 (w:w:w:w). The solidification process in SNEDDS was performed using HDK N20 Pharma as a solid carrier.Results: The amorphous microspheres appeared spherical with significantly decreased particle size compared to the drug powder. The crystalline microspheres exhibited a rough surface with no major particle-size difference compared with sildenafil powder, indicating that the hydrophilic excipients adhered to the sildenafil crystal. Solid SNEDDS presented a smooth surface, assuming that the oily liquid was adsorbed to the porous solid carrier. According to the physicochemical evaluation, the crystalline state maintained in crystalline microspheres, whereas the crystal state changed to amorphous state in other formulations. Amorphous microspheres, crystalline microspheres and solid SNEDDS produced about 79, 55, 82-fold increased solubility, compared to drug powder. Moreover, the prepared formulations provided a higher dissolution rate (%) and plasma concentration than did the drug powder (performance order; solid SNEDDS ≥ amorphous microspheres ≥ crystalline microspheres > drug powder). Among the formulations, solid SNEDDS demonstrated the highest improvement in oral bioavailability (AUC; 1508.78 ± 343.95 h·ng/mL).Conclusion: Therefore, solid SNEDDS could be recommended as an oral dosage form for enhancing the oral bioavailability of sildenafil.Keywords: sildenafil, amorphous microspheres, crystalline microspheres, solid self-nanoemulsifying drug delivery system, aqueous microenvironment, oral bioavailability